The effect of dysmenorrhea gymnastics on reducing the level of menstrual pain (dysmenorrhea) - Emelya, Seska; Primadevi, Inggit; Kumalasari, Desi; Sanjaya, Riona (Journal of Current Health Sciences, 2023)
Dysmenorrhea is experienced chiefly in women with menarche age 12 years, 83.7%. Its prevalence in adolescents ranges from 43% to 93%, where about 74-80% of adolescents experience mild dysmenorrhea. One of the sports that can treat menstrual pain is dysmenorrhea gymnastics. This study aimed to determine the effect of dysmenorrhea gymnastics on reducing the level of menstrual pain in adolescent girls at Vocational High School YP 17 Baradatu in 2022. This type of research was quantitative research with a pre-experimental design and a one-group pretest and posttest design approach. The population in this study was all students of class X Vocational High SchoolYP 17 Baradatu with 79 people with a sample of 15 people. The sampling technique used was purposive sampling. While the data analysis used was Wilcoxon. This study indicates that the average menstrual pain before dysmenorrhea gymnastics in adolescent girls was 4.33. Meanwhile, after the treatments, the average is 1.47. The bivariate analysis results showed an effect of dysmenorrhea gymnastics on decreasing menstrual pain in adolescent girls at Vocational High School YP 17 Baradatu in 2022 with a p-value of 0.001. It is expected that students can apply dysmenorrhea gymnastics when experiencing dysmenorrhea pain. They also can teach their friends who experience menstrual pain. Abstrak: Dismenore banyak dialami pada wanita dengan usia menarche ≤ 12 tahun yaitu sebanyak 83,7%. Prevalensi kejadian dismenore pada remaja berkisar antara 43% hingga 93%, dimana sekitar 74-80% remaja mengalami dismenore ringan. Salah satu olahraga yang dapat digunakan untuk mengatasi nyeri haid adalah dengan senam dismenorea. Tujuan penelitian ini untuk mengetahui pengaruh senam dismenore terhadap penurunan tingkat nyeri haid (dismenore) pada remaja putri di SMK YP 17 Baradatu tahun 2022. Jenis penelitian ini adalah penelitian kuantitatif yaitu dengan rancangan pre-experiment dan pendekatan one group pretest and posttest design. Populasi dalam penelitian ini adalah seluruh siswi kelas X SMK YP 17 Baradatu dengan jumlah 79 orang dengan sampel 15 orang. Teknik sampel yang digunakan yaitu purposive sampling. Analisis data menggunakan wilcoxon. Hasil penelitian ini menunjukkan bahwa rata-rata nyeri haid sebelum melakukan senam dismenore pada remaja putri adalah 4,33 dan setelah dilakukan senam dismenore didapatkan rata-rata 1,47. Hasil analisis bivariat didapatkan ada pengaruh senam dismenore terhadap penurunan tingkat nyeri haid (dismenore) pada remaja putri di SMK YP 17 Baradatu tahun 2022 dengan p value 0,001. Diharapkan siswi dapat menerapkan senam dismenore saat mengalami nyeri dismenore, serta dapat mengajarkan kepada teman-temannya yang mengalami nyeri haid.